Damselflies overcome color saturation barriers of photonic glasses via pigment loading and refractive index modulation - Tali Lemcoff; Lotem Alus; Albert Batushansky; Yahel Fishman; Nila Theodor; Keshet Shavit; Lahav Hyitner; Almut Kelber; Johannes S. Haataja; Dan Oron; Benjamin A. Palmer (Proceedings of the National Academy of Sciences, 2026)
Biological strategies for manipulating light have revealed new concepts in light scattering, inspiring the design of sustainable photonic materials. While iridescent optical systems have been extensively studied, many applications require noniridescent structural colors which are much more difficult to achieve. Photonic glasses, comprising randomly arranged dielectric spheres, offer a promising solution toward such structural colors. However, their intrinsic disorder and particle size polydispersity typically lead to poor color saturation. Here, we identify two strategies employed by certain damselflies to generate unexpectedly vivid, tunable angle-independent colors from a photonic glass. First, doping of transparent pteridine nanospheres with yellow pigments strengthens blue–green reflectance resonances by simultaneously absorbing off-resonant wavelengths and enhancing the refractive-index near the reflectance band. Second, the refractive index of the nanospheres is modulated, via changes in crystallinity, to be almost exactly inversely correlated with nanosphere size. Thus, variations in nanosphere size, that ordinarily broaden reflectance resonances, resulting in poor color saturation, are compensated for by a correlated change in their refractive index. This ensures that even in a polydisperse ensemble, a consistent Mie scattering size parameter is maintained, strengthening short-range correlations and Mie scattering resonances. Finally, we show how damselflies tune these structural colors during maturation by precisely modulating the average size of the nanospheres, which arises naturally during the development of the pigment cells due to the densification and crystallization of the nanospheres. These findings reveal design strategies for overcoming limitations in the saturation of disordered photonic systems.